Analisis Risiko Sebagai Upaya Peningkatan Mutu Pendidikan Di Sekolah - Mulyani, Mulyani; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
This study aims to analyze the role of risk analysis in supporting the improvement of education quality in schools. The issue raised focuses on the suboptimal implementation of risk management in the planning, implementation, and evaluation processes of education quality. This study employs a qualitative descriptive approach with a literature review method. Data were obtained through systematic searches of scientific journals, risk management textbooks in education, and relevant previous research from the last ten years. The analysis was conducted by categorizing findings based on risk analysis stages: identifying risk sources, determining impact levels, and control strategies that support school quality improvement. The findings indicate that the application of risk analysis helps educational institutions recognize potential quality barriers early, establish improvement priorities, and guide decision-making more effectively. This study concludes that integrating risk analysis into the school's internal quality assurance system contributes to creating sustainable and adaptive education management in response to environmental changes.